2022
DOI: 10.3390/jmmp6040083
|View full text |Cite
|
Sign up to set email alerts
|

Areal Analysis Investigation of Selective Laser Melting Parts

Abstract: Selective laser melting is an additive manufacturing technology used to fabricate metal parts characterized by complex geometries that are difficult or impossible to produce with conventional production methods. One of the major drawbacks of laser melting is the poor surface quality that typically is not satisfactory for functional applications. The aim of this work is to use areal analysis to characterize selective laser melting surfaces. The results highlight a marked variability and anisotropy that cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…By modifying the lateral overlap between adjacent beads, Bernauer et al demonstrated that an optimal overlapping distance exists, at which good wettability and surface quality can be achieved [56,125]. Sheikh et al measured the average surface roughness (R a ) [147] of layers deposited using different lateral overlap ratios and achieved an R a lower than 8 µm for the optimum overlap ratio employing SS304 wire with a 100 μm diameter as depicted in Figure 17 [65]. Consistent with these findings, several studies stated that exceeding the optimal lateral overlap leads to reduced material efficiency and accuracy, whereas low lateral overlap compromises surface topography [58,148].…”
Section: Single-track Depositionmentioning
confidence: 99%
“…By modifying the lateral overlap between adjacent beads, Bernauer et al demonstrated that an optimal overlapping distance exists, at which good wettability and surface quality can be achieved [56,125]. Sheikh et al measured the average surface roughness (R a ) [147] of layers deposited using different lateral overlap ratios and achieved an R a lower than 8 µm for the optimum overlap ratio employing SS304 wire with a 100 μm diameter as depicted in Figure 17 [65]. Consistent with these findings, several studies stated that exceeding the optimal lateral overlap leads to reduced material efficiency and accuracy, whereas low lateral overlap compromises surface topography [58,148].…”
Section: Single-track Depositionmentioning
confidence: 99%